Analysis of similarities between savings for housing carried out in the military and police housing development fund (Honor Fund) and a savings and construction promotion account (AFC account) (2021)
The present analysis of savings accounts to promote construction "AFC Accounts" aims to identify and show the main characteristics of these accounts, and the different benefits created for those who invest in them, as well as to identify the similarities with the savings accounts for housing in which the active members of the Military Forces and the National Police linked to the Honor Fund invest, who intend to acquire new or used housing, seeking to achieve the classification of them as an AFC account and thus Obtain tax benefits for the personal assets of the Armed Forces obliged to declare income.